Mapping key trends, relationships, and molecular pathways for neuroprotection in glaucoma: a bibliometric approach - Puneet Agarwal; Renu Agarwal; Igor Iezhitsa (International Journal of Ophthalmology)
Glaucoma, a degenerative optic neuropathy, causes retinal ganglion cell (RGC) apoptosis and irreversible vision loss. Current therapies often fail to stop disease progression despite lowering intraocular pressure, the main risk factor. Thus, neuroprotective strategies have gained interest. We performed a bibliometric analysis to determine global publishing trends and relationships among prolific authors, publications, institutions, funding agencies, and journals. We also analyzed author keywords to identify research hotspots in glaucoma neuroprotection. Further, based on keyword analysis, we reviewed most recent literature to understand mechanistic pathways underlying glaucoma-related pathophysiological responses leading to RGC loss. Bibliographic data were sourced from Scopus. Basic bibliographic features were characterized using Scopus's functions. VOSviewer was used for mapping and visualizing bibliometric networks. The analysis included trends in publications since 2000, the most prolific countries, institutions, authors, and the strength of their linkages. A significant increase in publication output over the past two decades was noted. The United States leads in funding support, research output, and citation links, followed by China and the UK. Among the top 10 most cited authors, three are from Japanese institutions. Keyword analysis shows a focus on molecular targets related to ischemia, excitotoxicity, inflammation, and oxidative stress, with fewer emerging drug candidates and limited clinical trials. Based on the most recent literature, emerging molecular targets underlying these key pathophysiological mechanisms are summarized. In conclusion, while pathophysiology and molecular mechanisms are the current focus, there is not much progress in developing new drug candidates and conducting clinical trials.